Pengembangan Ludo Word Game (LWG) Kimia sebagai Media Pembelajaran pada Materi Zat Aditif dan Zat Adiktif Kelas VIII SMP - Silvia Darma, Iswendi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Chemistry Ludo Word Game is one of learning media in a game form as variousexercise for establishing students’ concept. This study aim to produce Chemistry LudoWord Game as learning media in Additives and Addictive material and to validity andpracticality level as media function. The lands of this research is Research andDevelopment study with 4-D models: (1) define, (2) design, (3) develop, and (4)disseminate. This media was validated by four Chemistry Lecturers of FMIPA UNP andScience Teacher of SMPN 7 Padang. The Practicality level was done by two ScienceTeacher of SMPN 7 Padang and 32 students of IX.2 class SMPN 7 Padang. It usedvalidity and practicality questionnaire as instrument. Data collection technique wasdone by questionnaire distribution and was analyzed by Kappa Cohen formula. Theresult shows that Chemistry Ludo Word Game as learning media in Additives andAddictives material has 0,79 validity and categorized as very high validity and 0,84practicality and categorized as very high practicality. This data means Chemistry LudoWord Game as developed media can be used as learning media in Additives andAddictive material.Keyword : Ludo Word Game (LWG) Chemistry, learning media, addictive, researchand development, 4-D models